Radiography may not be accurate in assessing acute ankle sprains in children - Xiongtao Li; Xiantao Shen; Si Wang; Jie Sun; Zhaoting Liu (Journal of Orthopaedic Surgery and Research)
Abstract Background Acute ankle sprains are among the most common injuries in children and are often associated with chondral avulsion fractures and ligament injuries. However, radiography may not be sufficiently accurate for assessing cartilage and ligament injuries in children. The primary purpose of this study was to evaluate the necessity of radiography in the diagnosis of acute ankle sprains in children. The secondary purpose was to assess whether ultrasonography can effectively improve the diagnostic accuracy of acute ankle sprains in children. Methods We collected medical data from 78 children with acute ankle sprains who underwent both radiological and ultrasound examinations, 59 of whom also had ankle MRI results. The agreement between the radiographic and ultrasonographic findings in these 78 patients was assessed via Cohen’s kappa and McNemar tests. Using MRI results as the gold standard, the sensitivity, specificity, positive predictive value, and negative predictive value of radiography and ultrasonography were evaluated for the 59 patients who had MRI results. Cohen’s kappa and McNemar’s tests were also utilized to assess the reliability of radiography and ultrasonography in comparison to MRI. Results Among the 78 children with acute ankle sprains, 29 did not show fractures on radiological examination, but fractures were detected via ultrasound examination. Among these 29 fractures, 20 were chondral avulsion fractures of the distal fibula, and 9 were avulsion fractures of the lateral talus process. The agreement between radiography and ultrasonography was fair (Kappa = 0.250), and the difference was statistically significant (P < 0.001). Using MRI as the gold standard, radiography resulted in 17 false-negative cases for lateral ankle fractures, with a sensitivity of only 47%. Ultrasonography produced only one false-negative case, achieving a sensitivity of 97%. Ultrasonography showed substantial agreement with MRI (Kappa = 0.797), whereas radiography showed fair agreement with MRI (Kappa = 0.384). Conclusions Acute ankle sprains in children frequently result in a high incidence of chondral avulsion fractures. However, radiography may be inadequate for accurately diagnosing these fractures. Reliance on radiography alone may lead to a substantial number of false-negative cases. Compared with radiography, ultrasonography is highly accurate in the diagnosis of chondral avulsion fractures and ligament injuries in children. We believe that ultrasonography, as a noninvasive, radiation-free, and cost-effective dynamic diagnostic method, is particularly suitable for the early diagnosis of acute ankle sprains in children. Level of evidence Level III; Diagnostic Study.